Web development & design foundations with HTML5 - Felke-Morris, Terry (Pearson Higher Education, 2019)
Web Development and Design Foundations with HTML5 introduces HTML and CSS topics such as text configuration, color configuration, and page layout, with an enhanced focus on the topics of design, accessibility, and Web standards. The text relates both the necessary hard skills (such as HTML5, CSS, and JavaScript) and soft skills (design, e-commerce, and promotion strategies) considered fundamental to contemporary web development.